Efek Budaya Negara Terhadap Agresivitas Pajak Dengan Moderasi Persepsi Atas Korupsi: Pendekatan Multicountry - Bagas Aldhian; Theresia Woro Damayanti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
National culture in each country needs to be considered because it can be one of the factors of tax agressiveness. In this study several dimensions including distance of power, individualism, uncertainty and masculinity of a person can carry out acts of tax agressiveness.. However, the distance of power, individualism, uncertainty and masculinity can change when there is corruption in the country. The purpose of this study is to look at the influence of power distance, individualism, uncertainty, and masculinity by adding moderation variables, namely corruption against someone to carry out acts of tax agressiveness.. In this study the data used are secondary data, obtained from the World Bank’s Enterprise Survey (WBES) in 2006 to 2018. In analyzing these data using Multinomial Logistic Regression (MLR). This sudy confirmed that masculinity effect tax agressiveness but power distance, individualism, uncertainty not effected on tax agressiveness. Moreover, corruption has influence the relationship between masculinity and tax agressiveness.